2008
DOI: 10.1016/j.stem.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Zfh-1 Controls Somatic Stem Cell Self-Renewal in the Drosophila Testis and Nonautonomously Influences Germline Stem Cell Self-Renewal

Abstract: Summary The ability of adult stem cells to maintain their undifferentiated state depends upon residence in their niche. While simple models of a single self-renewal signal are attractive, niche-stem cell interactions are likely to be more complex. Many niches have multiple cell types, and the Drosophila testis is one such complex niche with two stem cell types, germline stem cells (GSCs) and somatic cyst progenitor cells (CPCs). These stem cells require chemokine activation of Jak/STAT signaling for self-renew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
548
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(578 citation statements)
references
References 50 publications
30
548
0
Order By: Relevance
“…Similar trends were also observed when Hh signaling activity was manipulated through altering Hh or Ptc expression level (Supplementary information, Figure S3). In addition, Smo 3 and Ptc IIW null alleles were used to inactivate and activate Hh signaling, respectively, in mosaic analysis with a repressible cell marker (MARCM). The results showed that Smo 3 mutant CySCs disappeared rapidly, while Ptc IIW mutant CySCs were found in all testes (Supplementary information, Table S1, Figures S4 and S5), which is consistent with the recent findings by others [7].…”
Section: -Positive Cells Under Different Hh Signaling Activities (Sumentioning
confidence: 99%
See 2 more Smart Citations
“…Similar trends were also observed when Hh signaling activity was manipulated through altering Hh or Ptc expression level (Supplementary information, Figure S3). In addition, Smo 3 and Ptc IIW null alleles were used to inactivate and activate Hh signaling, respectively, in mosaic analysis with a repressible cell marker (MARCM). The results showed that Smo 3 mutant CySCs disappeared rapidly, while Ptc IIW mutant CySCs were found in all testes (Supplementary information, Table S1, Figures S4 and S5), which is consistent with the recent findings by others [7].…”
Section: -Positive Cells Under Different Hh Signaling Activities (Sumentioning
confidence: 99%
“…These results demonstrate that Hh signaling acts in parallel with JAK-STAT signaling to promote CySCs self-renewal, and that enhanced Hh signaling activities can compensate for the loss of Stat92E activity to maintain CySCs. In Drosophila testis niche, GSCs could be regulated by CySCs through CySC-secreted BMP as a niche signal as well as cell competition between GSCs and CySCs [3,8]. To determine whether Hh signaling affects GSCs through CySCs, we quantified GSC number after altering Hh activities in cyst cells (Supplementary information, Data S1).…”
Section: -Positive Cells Under Different Hh Signaling Activities (Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, activity of Stat in the germline is essential for continued attachment of GSCs to the hub and retains GSCs in their niche (13). Several lines of evidence suggest that CySCs provide a niche for maintenance of GSCs (13)(14)(15). Consistent with this model, it has been proposed that self-renewal of GSCs is specified by instructive signal(s) from the CySCs, with a likely candidate being TGF-β signaling (13).…”
mentioning
confidence: 97%
“…The let-7-Imp axis regulates ageing of the Drosophila testis stem-cell niche [170]. More often, micro niche affect oocyte formation by mitotically active germ cells obtained from ovaries of reproductive-age women [174].…”
Section: Regenerative Gonadial Tissue Damage Repairingmentioning
confidence: 99%